N-Terminal-Dependent Protein Degradation and Targeting Cancer Cells - Eldeeb, Mohamed A. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Intracellular protein degradation is mediated selectively by the Ubiquitin-Proteasome System (UPS) and autophagic-lysosomal system in mammalian cells. Many cellular and physiological processes, such as cell division, cell differentiation, and cellular demise, are fine-tuned via the UPS-mediated protein degradation. Notably, impairment of UPS contributes to human disorders, including cancer and neurodegeneration. The proteasome- dependent N-degron pathways mediate the degradation of proteins through their destabilizing aminoterminal residues. Recent advances unveiled that targeting N-degron proteolytic pathways can aid in sensitizing some cancer cells to chemotherapeutic agents. Furthermore, interestingly, exploiting the N-degron feature, the simplest degradation signal in mammals, and fusing it to a ligand specific for Estrogen-Related Receptor alpha (ERRa) has demonstrated its utility in ERRa knockdown, via N-terminal dependent degradation, and also its efficiency in the inhibition of growth of breast cancer cells. These recent advances uncover the therapeutic implications of targeting and exploiting N-degron proteolytic pathways to curb growth and migration of cancer cells.
Keywords: proteasome